Development Of Digital Quiz Media For The Probability Topic (Grade XI) - Leny Nurkholisah M; Olief Ilmandira Ratu Farisi (Civiliza Publishing, Indonesia., 2026)
This study aimed to develop a Nearpod-based digital quiz medium for teaching probability in Grade XI and to determine its validity and practicality. The study employed the Research and Development (R&D) method using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation. The participants were 20 Grade XI students at MAN 1 Probolinggo. Data were collected through material expert validation sheets, media expert validation sheets, student response questionnaires, and learning outcome tests. Quantitative descriptive analysis was used to determine the validity and practicality of the developed media. The results showed that the material expert validation reached 89.1%, while the media expert validation reached 93.75%, both categorized as highly valid. Student responses obtained a score of 90.25%, indicating that the media was highly practical. Furthermore, students achieved an average quiz score of 82.5, exceeding the school's Minimum Mastery Criterion (75). These findings indicate that the Nearpod-based digital quiz medium is valid, practical, and appropriate for supporting mathematics learning on the topic of probability in Grade XI.